Destination image on the DMO's platforms: official website and social media - Molinillo,Sebastian (2017)
Tourists usually configure and develop ideas about possible destinations based on information previously gathered from both social media and the official web of the destination management organization (DMO). In spite of the relevance of said information sources, there have not been many studies evaluating how these different sources influence the destination image. This research proposes a model intended to explain the image creation process of a destination taking into account both the DMO's online platforms and the perceived psychological distance. The proposed model is tested with an empirical study including a questionnaire which collects data from 264 participants. The validity of the model is reviewed through PLS analysis. Results show that the psychological distance does not influence the overall destination image. In addition, the overall destination image can be estimated to a larger extent when tourists approach social media as their main source of information. Implications and conclusions are discussed